IN-VITRO ANTICANCER ACTIVITY OF MICHELIA CHAMPACA L. FLOWERS AGAINST EHRLICH ASCITES CARCINOMA CELL LINE - T.ANANTHI; M.CHITRA; B.ARUNA (International Journal of Pharma and Bio Sciences, 2014)
Cancer is a disease in which there is an uncontrolled multiplication and spread, within the body, of abnormal forms of the body’s own cells. Assessment of In-vitro cytotoxicity has been recently become popular as a primary screening method for evaluating anti-cancer activities of various natural source. This study was carried out to characterize anti-cancer activity of methanolic extract of Michelia champaca L. flower on Ehrlich Ascites carcinoma cell line [EAC] by Trypan Blue Dye exclusion method and MTT [(3-(4,5 dimethyl thiazol-2-yl) 2,5-di phenyl tetrazolium bromide] assay. The preliminary phytochemical analysis was also carried out. Cell viability, inhibition was determined by Trypan blue dye exclusion method. The results showed that the methanolic extract of Michelia champaca L. decreased cell viability and increased growth inhibition in a concentration dependent manner and also altered the cell morphology. Michelia champaca L. methanolic extract has a significant anticancer effect against EAC cell line concentration range between 50μg to 150μg by using MTT assay. The minimum inhibition of plant extract showed 13.95% at 50μg/ml and maximum inhibition 54.46% was observed at 150μg/ml. IC50 value of Michelia champaca L. on EAC cell line was 147.5μg/ml by MTT assay. From the results, it showed that the methanolic extract of Michelia champaca L. has potent anti-cancer activity on EAC Cell line.